2009
DOI: 10.1007/s00464-009-0652-7
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal recovery after laparoscopic colectomy: results of a prospective, observational, multicenter study

Abstract: Mean GI recovery and LOS after LC were accelerated compared with those for patients in open laparotomy bowel resection clinical trials or those reported in large hospital databases (0.7 and 1.7-2.2 days, respectively). Overall POI-related morbidity was similar between the open bowel resection and LC populations, demonstrating that POI continues to present with important morbidity regardless of the surgical approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(54 citation statements)
references
References 46 publications
2
50
1
1
Order By: Relevance
“…POI has been characterized as an independent predicting factor for a prolonged LOS [17] and as the major factor accounting for in hospital morbidity regardless the type of operation [18]. Laparoscopy as part of the ERAS concept with limited surgical trauma has been shown to reduce POI significantly [19].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…POI has been characterized as an independent predicting factor for a prolonged LOS [17] and as the major factor accounting for in hospital morbidity regardless the type of operation [18]. Laparoscopy as part of the ERAS concept with limited surgical trauma has been shown to reduce POI significantly [19].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, nonmedical reasons like outpatient resources or limited social care facilities challenge LOS [10]. The use of laparoscopy significantly reduced LOS [18] and is therefore an implemented part of ERAS. In contrast, the use of epidural analgesia, one of the items in the Consensus Guidelines [3], has no effect on LOS and mobilization [26,27] and hence should be critically investigated as to its impact on LOS and ERAS.…”
Section: Resultsmentioning
confidence: 99%
“…Also, much data have accumulated on techniques to prevent postoperative ileus especially after abdominal procedures including the use of thoracic epidural analgesia, peripheral opioid antagonists, laxatives, chewing gum, intravenous local anaesthetics and avoidance of routine nasogastric intubation and fluid excess [39][40][41][42][43]. Importantly, opioids should be avoided because of the gastrointestinal effects as also emphasised when comparing open vs. laparoscopic procedures [39,44] since the benefits of a laparoscopic approach may be overridden by use of opioids. What is needed now is better design including all components of the fast-track methodology and to define the exact role of each technique in relation to specific procedures.…”
Section: Nausea-vomiting (Ponv) and Ileusmentioning
confidence: 98%
“…van Bree et al reported laparoscopic surgery was a signifi cant independent predictive factor of improved colonic transit [ 85 ]. Delaney et al also showed mean bowel recovery and length of stay after laparoscopic colectomy was accelerated when compared with open colectomy [ 86 ].…”
Section: Ileusmentioning
confidence: 96%